A model for the prediction of the punching resistance of steel fibre reinforced concrete slabs centrically loaded - Moraes-Neto, B. N. (2013)
With the aim of contributing for the development of design guidelines capable of predicting with high accuracy the punching resistance of steel fibre reinforced concrete (SFRC) flat slabs, a proposal is presented in the present paper and its predictive performance is assessed by using a database that collects the experimental results from 154 punching tests. The theoretical fundaments of this proposal are based on the critical shear crack theory proposed by Muttoni and his co-authors. The proposal is capable of predicting the load versus rotation of the slab, and attends to the punching failure criterion of the slab. The proposal takes into account the recommendations of the most recent CEB-FIP Model Code for modelling the post-cracking behaviour of SFRC. By simulating the tests composing the collected database, the good predictive performance of the developed proposal is demonstrated.